A new species of Griseothosea (Lepidoptera, Limacodidae) from Wuyishan National Park, China - Zhang, Quanhong; Solovyev, Alexey V.; Liang, Jiamin; Wang, Min; Wang, Houshuai (Zootaxa, 2023)
A new species of Griseothosea nigrifasciata sp. nov. is described and illustrated from Wuyishan National Park, Fujian province, China. It differs from other members of Griseothosea by the male genitalia: uncus with strongly curved lateral margin, juxta with two finger-shaped protrusion apically, and aedeagus shorter and slenderer. The new species is supported molecularly by the analysis of a 658 bp fragment of the COI gene. A key to Griseothosea is provided.